The Effectiveness of a Local Wisdom-Based Science E-Module on Students’ Learning Outcomes in Additive Substances - Hilwannisa, Hilmi Ufairah; Enawaty, Eny; Mayasari, Eni (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to examine the differences in students' learning outcomes before and after the implementation of a local wisdom-based science e-module in junior high school, as well as to evaluate the effectiveness of the e-module on learning outcomes. The study employed an experimental method with a one-group pretest-posttest design. The sample consisted of 15 eighth-grade students from SMP Karunia Selakau, selected through total sampling. Data were collected using pretests and posttests to measure improvements in learning outcomes. The data were analyzed using the Shapiro-Wilk normality test and the Wilcoxon Signed-Rank test due to non-normal distribution. The results revealed a significant difference in learning outcomes following the use of the local wisdom-based e-module, with an Asymp. Sig value of <0.001. The average pretest score of 45.33 increased to 89.33 in the posttest. The N-Gain analysis showed a score of 0.78, categorized as high, while the effect size of 0.89 indicated a strong level of effectiveness. These findings suggest that the use of a local wisdom-based e-module successfully enhances students' learning outcomes in the topic of food additives and can serve as an innovative alternative teaching material in science education.